Analysis Of Using #1hari1oknum and #percumalaporpolisi Hashtags in The Computer Mediated Communication Function On Instagram - Susanto, Farid; Sufa, Siska Armawati; Brumadyadisty, Garry; Jusnita, R. Ayu Erni; Eko Putro, Hartopo (Jurnal Komunikasi Universitas Garut: Hasil Pemikiran dan Penelitian, 2024)
This research examines the pattern of incidents related to police institutions on Instagram's social media platform, focusing on the hashtags #percumalaporpolisi and #1hari1oknum. It also tries to explain the role and purpose of using these hashtags in the context of computer-mediated communication (CMC) practices on Instagram. This research uses a qualitative methodology, utilizing data collection procedures through social media analysis, analysis of hashtag use, literature review, and other similar methods. This research documentation involved examining digital content on Instagram's social media platform, primarily visual content accompanied by written explanations. This research analysis began by searching for phrase content using the hashtags #1hari1oknum and #percumalaporpolisi on Instagram social media. The findings show that CMC uses various strategies utilizing hashtags on the social media platform Instagram. The hashtag (#) functions as an identifier for themes and a repository for information about items related to police agency performance. This hashtag will collect data about incidents related to the credibility of police agencies. Apart from that, the hashtag contains the latest issues regarding violations of authority committed by police officers involved in violations or unethical behavior. This shows that individuals who utilize social media platforms produce personalized content.